El arte de gobernar moderno: o de la constitución de una ciencia de la educación = The art of modern govern: or the establishment of a science of education - Marín-Díaz, Dora Lilia; Noguera-Ramírez, Carlos Ernesto (Educação, 2013)
This article analyzes the constitution of some knowledge, ideas, concepts and practices in the field of pedagogical knowledge and as a result of concern for the government of self and others. Such a situation is presented as evidence to explain that the government found in pedagogical practices (teaching, training, education, learning), and perhaps its main-its most efficient form of deployment. They are designated two points: 1) the emergence, between the sixteenth and seventeenth, the Teaching as knowledge and with it notions of instruction and teaching, which express a way of thinking the government of individuals and populations as part of the deployment a set of devices disciplinary emphasis of government, 2) the emergence, between the eighteenth and nineteenth centuries, the notion of “education” in pedagogical discourses linked to the shift of emphasis from disciplinary devices to the devices of liberal government. Thus, the analysis performed by using the notion Foucault and governmentality, which serve as a methodological tool in this study clearly refer a set of practices and pedagogical knowledge of which he took and that the present analysis attempts to describe